Effect of natural and forced charge air humidity on the performance and emissions of a compression-ignition engine operating at high warm altitude. (1st March 2023) - Serrano, José Ramón; Martín, Jaime; Piqueras, Pedro; Tabet, Roberto; Gómez, Javier
Abstract: The effect of ambient humidity on the performance and pollutant emissions of internal combustion engines is not considered in the literature despite type-approval criteria are moving closer to real driving conditions. This work analyses experimentally the effects of charge air humidity at high warm altitudes, where the use of exhaust gas recirculation (EGR) is typically lowered and even avoided to recover engine performance at the expense of NOx emissions increase, on the response of a compression-ignition engine under a wide range of steady-state conditions in terms of engine-out emissions and specific fuel consumption. The impact of specific humidity variations within the atmospheric range was analysed by coupling the engine to an altitude simulator with pressure, temperature, and humidity control capabilities. High altitudes and warm & high ambient temperatures were explored (2000 m at 30 °C and 2500 m at 45 °C) to cover ambient specific humidity up to 30 gwater /kgdry_air . In addition, the effects of increasing the specific humidity above the atmospheric levels were considered at 2500 m and 45 °C to emulate forced injection of water in the engine intake line corresponding to 60 gwater /kgdry_air . With this approach, understanding of the role of humidity is provided to highlight its importance as additional ambient property in emission control. In parallel, the assessment of the forced water content increase to control NOx emissions when EGR must be lowered was performed due to the altitude impact on the engine performance and turbocharger limits. The results showed a consistent and significant reduction in engine-out NOx emissions as the ambient humidity increased, reaching up to 300% with respect to the dry case, caused by the decrease in O2 availability due to the water content increase. The benefits of high humidity in NOx emission control at high altitudes when EGR is not feasible were complemented by an improved trade-off with particulate matter emission compared to the standard from EGR use. The results evidenced a reduction in opacity close to 250% for a given engine-out NOx emission when EGR was replaced by water content. By contrast, the slowdown of the combustion process as the fresh air humidity increased deteriorated the specific fuel consumption significantly as the engine load and speed increased. Nevertheless, these penalties ranged from 2 to 2.7% in the worst conditions and showed the same sensitivity for EGR and humidity increases. Highlights: Effect of humidity on CI engines demonstrated regardless of other ambient variables. Altitude & humidity conditioning system to emulate Earth and forced water content. Humidity reduces O2 by dilution, volumetric efficiency, and gas constant penalties. High water content reduces NOx and improves the trade-off with PM compared to EGR. Forced water injection as a substitute and/or complement of EGR in altitude operation.